(Arm) Wrestling with Masculinity: Television, Toughness, and the Touch of Another Man's Hand. (December 2019) - Diffrient, David Scott
For decades, dating back to the medium's origins as a commercially viable form of mass communication in the postwar years, US television programs have contributed to the many paradoxes of masculinity, revealing but also obscuring the normativizing function of cultural representations through the use of generic encoding and the compositional "logic" of male (visual) dominance. One visual motif in particular—the shot of two men sitting at a table, their hands temporarily locked as part of an arm wrestling contest—is noteworthy, given the frequency of its recurrence in a variety of fictional programming ( All in the Family, The Odd Couple, The Mary Tyler Moore Show, Taxi, etc.) as well as for its literal staging of masculinity as spectacle, as an object of spectatorial contemplation vis-à-vis the televisual construction of "toughness" as an inherently male attribute. If television and toughness can be said to go "hand in hand, " then the actual sight of two men joined together in a physical contest hints at the idea that intimacy is at much a part of such ritualized representations as intimidation is. Indeed, what several of the episodes discussed in this article (selected from representative television programs of the 1960s, 1970s, and 1980s) reveal is that a man is sometimes at his most unguarded—his most forthcoming and honest—when seated opposite another man during an arm wrestling match, a moment that is deserving of consideration as a symptomatic illustration of masculinity's paradoxes. Inspired by the early writings of Roland Barthes, in particular the French philosopher's essay "The World of Wrestling" (published as part of his 1957 book Mythologies ), I ultimately hope to reveal how seemingly innocuous images are "invested with ideological meanings, " unwittingly revealing what they often seek to conceal.